2015
DOI: 10.1021/nn506834r
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Large-Area Annular Cavity Arrays with Tunable Cylindrical Surface Plasmons for Sensing

Abstract: Surface plasmons that propagate along cylindrical metal/dielectric interfaces in annular apertures in metal films, called cylindrical surface plasmons (CSPs), exhibit attractive optical characteristics. However, it is challenging to fabricate these nanocoaxial structures. Here, we demonstrate a practical low-cost route to manufacture highly ordered, large-area annular cavity arrays (ACAs) that can support CSPs with great tunability. By employing a sol-gel coassembly method, reactive ion etching and metal sputt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 54 publications
(90 reference statements)
1
41
0
Order By: Relevance
“…The detection limits of the hybrid substrates are found to be 10 −12 m , implying that the hybrid substrates can be utilized for practical biomolecular sensing applications. [ 37–39 ] The collected signal intensities of 100 individual points from different concentrations are plotted in the scatter diagram shown in Figure 4e. It is observed that even at dilute concentrations not only the intensity distributions are narrow (for concentrations 10 −8 , 10 −10 , and 10 −12 m , the RSD = 2%, 5%, and 4%, respectively) but also a good linear relationship is obtained (Figure 4f).…”
Section: Figurementioning
confidence: 99%
“…The detection limits of the hybrid substrates are found to be 10 −12 m , implying that the hybrid substrates can be utilized for practical biomolecular sensing applications. [ 37–39 ] The collected signal intensities of 100 individual points from different concentrations are plotted in the scatter diagram shown in Figure 4e. It is observed that even at dilute concentrations not only the intensity distributions are narrow (for concentrations 10 −8 , 10 −10 , and 10 −12 m , the RSD = 2%, 5%, and 4%, respectively) but also a good linear relationship is obtained (Figure 4f).…”
Section: Figurementioning
confidence: 99%
“…Thanks to Padilla et al, the perfect metamaterial absorber (PMA) was first proposed in 2008 in the field of electromagnetic waves, and thus PMAs has been developed rapidly [ 1 ]. In recent years, there has been a great need for perfect absorbers (PAs) in stealth [ 2 , 3 ], photovoltaics technology, sensors [ 4 , 5 ], and other opto-electronic devices [ 6 , 7 ]. High-resolution manufacturing technologies for nanostructures are becoming more common as they are updated, and PMAs are receiving more and more attention due to their multiple light control functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, annular aperture arrays have drawn a wide research interest in the color filter [24,25], thresholdless nanolaser [26], and quarter-wave plates [27] in the visible range. However, there are few reports about annular aperture arrays for the application of biosensors [28].…”
Section: Introductionmentioning
confidence: 99%